KLASIFIKASI PENYAKIT PARU-PARU DENGAN MENGGUNAKAN METODE NAÏVE BAYES CLASSIFIER - Muhammad Yusril Haffandi; Elin Haerani; Fadhilah Syafria; Lola Oktavia (Politeknik Bisnis Indonesia, 2022)
The lungs are one of the organs of the human body that are very important in the process of respiration. There are several types of lung diseases, including Asthma, Bronchitis, Dyspnea, Pneumonia, COPD, and Tuberculosis. There are difficulties in the classification process, because the symptoms shown by sufferers have similarities between diseases. The purpose of this research is to classify lung disease using the Naive Bayes Classifier method. The choice of this method is because it only requires a small amount of training data to determine the estimated parameters needed in the classification process. This research was conducted at the Regional General Hospital Major General HA Thalib City of Sungai Full from August 3 2022 to September 3 2022. The data taken was in the form of medical records of lung disease patients from July to August as many as 134 patient data containing 19 symptoms disease and 6 disease diagnoses. From the test results using the Rapidminer application and data separation in the form of 34 testing data and 100 training data with a data comparison of 7:3, an accuracy value of 97.06 was obtained.